PRINCIPAL LEADERSHIP, SCHOOL CLIMATE, AND ACHIEVEMENT MOTIVATION: HOW THEY AFFECT TEACHERS' WORK COMMITMENT - Ririyanti, Novi; Sitanggang, Nathanael; Daryanto, Eka (Education Administration Study Program, School of Postgraduate Studies, Universitas Riau, 2024)
The objective of this study was to examine the significant impact of principal leadership, school climate, and achievement motivation on teachers' work commitment in two private high schools in Medan. A quantitative research design was employed, using a descriptive correlational approach. The research involved all teachers from the two private high schools, consisting of 56 respondents. Data were collected through questionnaires and analyzed path analysis, validity tests, questionnaire reliability tests, linearity tests, and multiple linear regression analysis. The hypothesis testing results revealed the following: (1) Principal leadership has a direct impact on teachers' work commitment in the two private high schools in Medan; (2) School climate has a direct impact on teachers' work commitment in these schools; (3) Achievement motivation also has a direct effect on teachers' work commitment; and (4) Principal leadership, school climate, and achievement motivation collectively exert a direct influence on teachers' work commitment in the two schools. The findings demonstrate that principal leadership, school climate, and achievement motivation together have a significant positive impact on teachers' work commitment. This implies that enhancing teacher performance in these schools can be achieved through strong principal leadership, a supportive school climate, and increased achievement motivation among teachers.